Management of Teacher Competency Development in the Madrasah Ibtidaiyah Negeri - Zebua, Armansyah; Hanum, Azizah; Nahar, Syamsu (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The goal of this research was to examine the Planning of Teacher Competency Development in Madrasah Ibtidaiyah Negeri 1 Gunung Sitoli City, the Organizing of Teacher Competency Development in Madrasah Ibtidaiyah Negeri 1 Gunung Sitoli City, the Implementation of Teacher Competency Development in Madrasah Ibtidaiyah Negeri 1 Gunung Sitoli City, and the Monitoring of Teacher Compet The data collection technique used interviews, observations, and documentary studies, while the standard data validity suggested by Lincoln and Guba consisted of credibility, transferability, dependability, and confirmability to strengthen the validity of the data found and the authenticity of the research. The technique used in planning teacher competency development is to collect all recommended programs, then discuss and discuss and decide which programs will be carried out, such as workshops, training, outbound, and programmatic delivery of teachers for every training held by the Ministry of Religion or other agencies.